The multi‐stage gasification process of low‐rank coal samples from gravity separation process - Mai, Thuan Duc; Sebe, Emese; Koós, Tamás; Kállay, András Arnold (Asia-Pacific journal of chemical engineering, 2024)
The separation process is a well‐established method for beneficiation technologies of low‐rank coal, especially in the case of utilization in the thermochemical processes. In this study, three coal samples, including the original low‐rank coal sample and two coal samples (C1 and C2) from the gravity separation process of the original coal sample, were gasified in a multi‐stage gasification process at the gasification temperature of 900°C and the steam‐to‐carbon (S/C) ratio of 1.00 and 1.25. The separation process led to a significant improvement in the quality of coal samples. This improvement is particularly characterized by a higher carbon and volatile fractions and a lower ash content compared with the original coal. This could be the main reason for the higher gasification performance in the case of the experiment of C1 and C2 coal samples. The volume of syngas obtained from gasification experiments of C1 and C2 samples increased between 1.3 and 1.5 times that of the original coal sample. At all S/C ratios and 900°C, the gasification experiment of the C2 sample produced the highest produced gas yield followed by the gasification experiment of the C1 sample. From the chemical point of view, the produced gas had an H2/CO ratio close to the desired ratio of 2.00, which is suitable for chemical synthesis processes. In the case of C1 sample experiments, the H2/CO ratios were 2.11 and 2.18 at S/C ratios of 1.00 and 1.25, respectively. For the experiments of the C2 sample, the H2/CO ratio reached 1.88 and 2.00 at S/C ratios of 1.00 and 1.25, respectively.